Reactivity as an attribute of a speaker’s temperament and acoustic characteristics of a speech sound wave. - Oziemski, Stanisław (Studia Psychologica: Theoria et praxis, 2002)
The research concerned a physical aspect of reactivity, expressed by acoustic characteristics of a speech sound wave, that is, changes of intensity and frequency in time. The research group consisted of 30 women, aged 20-24, 10 with high reactivity, 10 with low reactivity and the remaining 10 with average intensity of this feature, selected from among more than 360 students at three Warsaw colleges. The level of reactivity was measured by means of Formal Features of Behavior – Temperament Questionnaire (FCZ-KT) (Zawadzki, Strelau) and The Eysenck Personality Questionnaire – Revised (EPQ-R) (Brzozowski, Drwal) and the physical characteristics of a speech sound wave were measured in a soundproof cabin in the Institute of Basic Technical Problems of the Polish Academy of Sciences in the laboratory of Speech Acoustics and Cybernetics. The language material consisted of reading and spontaneous speaking on the subject of a picture. A statistically essential difference in respect of mean absolute slope (during readi  ), f0 ceiling (in the spontaneous speech), as well as the range and deviations of standard frequency of a speech sound wave in the group of high and low reactive persons has been demonstrated. Statistically essential correlation between the other psychological scales and acoustic parameters of a speech sound wave have also been stated.